Risks in Adolescent Adjustment by Internet Exposure: Evidence From PISA - Ortega-Ruipérez, Beatriz; Castellanos Sánchez, Almudena; Marcano, Beatriz (Frontiers in Psychology, 2021)
Problematic use and abuse of the Internet has manifested new risks among adolescents that affect academic, social, and emotional adjustment. In the academic domain, the role of Internet use on school performance and learning is studied, including the level of competence as a factor in this domain. On the social level, we measure how internet use affects school climate and problems related to bullying. On the emotional aspect, the relationship between internet use and satisfaction and positive feelings is studied, including well-being as a construct part of this domain. To find these relationships, data obtained from the Program for International Student Assessment survey, 2018 edition are used. Structural equation modeling was used to determine the most significant relationships between the aspects studied and internet use. Internet use includes four independent variables: two on abuse (time of use on a weekday outside of class and on a weekend) and two on problematic use (perception about forgetting time and perceived discomfort if the internet does not work). The results answer three research questions: (1) how the constructs created relate to the four independent variables on Internet usage, (2) how the observed variables respond to the latent constructs, and (3) how all these constructs are related to each other. These results highlight the need to teach young people to use the Internet in a useful and healthy way, as a preventive measure, and help professionals who detect technology abuse to act with effective measures to prevent the psychological consequences, working on the academic, social, and emotional aspects that have shown the greatest relationship. The problematic internet use is a complex problem and it is impossible and imprudent to relate it to isolated factors: it is necessary to consider different factors to better understand of the problem.